AN ENTERPRISE LEVEL ANALYSIS OF THE FACTORS AFFECTING BEEF PRODUCTION - N. Ertek; A. Keskin (Journal of Animal and Plant Sciences, 2019)
The purpose of this study was to perform an enterprise level analysis of the factors influencing production of beef. This analysis is based on a structural equation model projected by taking the social, technical and economic production aspects into account in unison. In the model, the cross-sectional data obtained from the surveys conducted with 256 farmers in the TRA region in 2015, was used. The results of the study indicated that the most crucial animal production infrastructure that has an impact on bovine meat production at enterprise level was the technical aspect. Within the scope of the animal production infrastructure, the type of barn, the ratio of the culture / mixed species within the entire feeder cattle population and the amount of the daily-consumed concentrate feed, were determined as the most important variables respectively. The structural equation model, when taken into account in a general manner, shows that the policy makers within the scope of the TRA region should prioritize structural policies aimed at improving and developing the technical structure of bovine meat production and should shift their support to this area.
Keywords: economic structure; animal production; TRA Region; Structural Equation Model; Turkey